"Nothing Short of Murder": How Leaders Can Diminish Military Capacities. (15th March 2022) - Piccolo, Samuel
Abstract: This article contends that civilian leaders can adversely affect military capacity in the realm of technology. I argue that if civilian leaders have personal biases that blind them to military effectiveness, and if they have the power to make unilateral procurement decisions, then military capacity will be hampered. With a main plausibility probe of Canada's disastrous World War I Ross rifle, I suggest that Minister of Militia Sam Hughes ensured that Canadians fought with the gun 18 months after its first wartime failures, failures so egregious that one officer said it was "nothing short of murder" to send soldiers into battle with it. I assess two shadow cases on rifle development and procurement involving Union war secretary Simon Cameron and British war secretary Hugh Arnold-Foster, both of which support my theory. I suggest that civilian control over specific military technologies is not desirable, and that civilian control of militaries in general may be strengthened by limiting control of these means of war.